The role of surface grinding, intermetallic precipitates and halide ions on zinc deposition and adhesion on aluminium cathode in zinc electrowinning - Nusen S. (2014)
Zinc deposition and adhesion on aluminium cathode in zinc electrowinning have been studied. Two different surface conditions of the aluminum cathode were performed i.e. polishing down to 3 μm and grinding by 800 grits emery paper. Short-time electrowinning to study initial zinc nucleation and long-time, pilot-scale electrowinning to study zinc adhesion were carried out in the presence of chloride ion up to 6.77 mM (0.24 g/l) or fluoride ion up to 1.05 mM (0.02 g/l) in the electrolytes. Corrosion of the aluminium cathode in the presence of these halide ions was studied by potentiodynamic and immersion tests. Microstructure of the aluminium cathode and morphology of zinc deposits were investigated by light and scanning electron microscopy. Discussion has been made regarding the role of surface grinding, intermetallic precipitates and halide ions on zinc deposition and adhesion related to sticking problem in the zinc extraction plant operation. © 2011 Elsevier B.V. All rights reserved.